Studi Kasus Penatalaksanaan Manajemen Penanggulangan Malaria Di Kabupaten Bulukumba - Eko Ardiansyah; Andi Susilawaty; Nurdiyanah Syarifuddin (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2015)
Malaria as a communicable disease a public health problem. The incidence of malaria in some districts in the province of South Sulawesi is still high in contrast with the incidence of malaria in the district Bulukumba are decreased, ie in 2010 about 2077 positive cases, in 2011 a total of 112 positive cases, in 2012 as many as 49 positive cases, and in 2013 as many as 51 cases , so it is important to know the incidence of malaria prevention management conducted in Bulukumba district.This study aims to describe the management of malaria control management to decrease the incidence of malaria conducted in Bulukumba. This research is qualitative descriptive. Informants in this study as many as 29 were determined through purposive sampling method. The data in this study are primary data and secondary data. Primary data obtained by depth interviews with informants and observation, while secondary data obtained from the data archive management of malaria in the relevant agencies.These results indicate that treatment of malaria is divided into two activities, namely the management of cases and management of risk factors. Case management consists of the discovery and treatment of patients, while the management of risk factors consist of vector control and environmental management. Type of malaria cases in the district Bulukumba in 2010 and 2011 is imported and local cases, while in the year 2012-2014 are all imported cases. Case detection is done through a survey method active, passive survey, mass blood examination, survey and survey contacts migration. Malaria treatment is done with combination therapy. Supervision of patient treatment is done by monitoring the treatment at the health center, direct visits to the homes of people health center staff, supervision by phone and direct monitoring by the family of the patient. Vector control activities beginning with a survey vector. Vector control is done through the distribution of mosquito nets, spraying homes and counseling. Environmental management activities are carried out, namely cleaning and shrub swamps, ponds and treatment by covering sewerage. Overall the parties involved in the management of malaria in the district Bulukumba is Bulukumba district health office, the health center, the non-governmental such as UNICEF and the Global Fund, the military (military and police), local governments, and communities.Suggestions for Bulukumba district health office for the activities of case detection through surveillance activities further improved migration seen malaria cases in the district in 2012-2014 Bulukumba an imported case. Keywords : Malaria, discovery of patient, patient treatment, Vector Control, Environmental Management